Prokineticin Is a New Linker between Obesity and Cardiovascular Diseases - Nebigil, Canan G. (Frontiers in Cardiovascular Medicine, 2017)
Obesity is a fast growing epidemic event worldwide. Fatness is associated with a number of comorbidities, including cardiovascular diseases (CVD). Although obesity can be heredity in 30% to 70% cases, the environmental contributions also play an important role in the increasing prevalence of obesity. The relationship between development of obesity and CVD are poorly characterized. Obesity and CVD can also be resulted from a common mechanism such as metabolic, inflammatory, and neurohormonal changes. Prokineticins are defined as cytokines (immunoregulatory proteins), adipokines (adipocyte-secreted hormone), angiogenic (increasing vessel formation) or aneroxic (lowering food intake) hormones. Prokineticin-mediated signaling plays a key role in the development of obesity and CVD. Two forms of prokineticins exist in circulation and in various tissues including the brain, heart, kidney, and adipose. Prokineticins act on the two G protein-coupled receptors (GPCRs) namely, PKR1 and PKR2. Prokineticin-2 via PKR1 receptor controls food intake and prevents adipose tissue expansion. The anti-adipocyte effect of PKR1 signaling is due to suppression of preadipocyte proliferation and differentiation capacity into adipocytes. Prokineticin-2/PKR1 signaling promotes transcapillary passages of insulin and increases insulin sensitivity. It also plays an important role in the heart and kidney development and functions. Here we discuss prokineticin-2 as a new adipocytokine in the association between obesity and CVD. We also highlight targeting PKR1 can be a new approach to treat obesity and CVD.